Dietary Tannic Acid Promotes Growth Performance and Resistance Against Aeromonas hydrophila Infection by Improving the Antioxidative Capacity and Intestinal Health in the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Liqin Ji; Yisen Shangguan; Chen Chen; Chengqing Wei; Junxian Zhu; Xiaoyou Hong; Xiaoli Liu; Xinping Zhu; Wei Li (Antioxidants)
To investigate the effect of tannic acid (TA) on the growth, disease resistance, and intestinal health of Chinese soft-shelled turtles, individual turtles were fed with 0 g/kg (CG), 0.5 g/kg, 1 g/kg, 2 g/kg, and 4 g/kg TA diets for 98 days. Afterwards, the turtles’ disease resistance was tested using Aeromonas hydrophila. The results showed that 0.5–4 g/kg of dietary TA increased the growth performance and feed utilization (p < 0.05), with 2.38 g/kg being the optimal level for the specific growth rate (SGR). The addition of 0.5–4 g/kg of TA in diets increased the mucosal fold height and submucosa thickness of the small intestine, which reached a maximum of 2 g/kg. The addition of 0.5–2 g/kg of TA effectively reduced the cumulative mortality that had been induced by A. hydrophila, with the 2 g/kg dosage leading to the lowest mortality. Additionally, 1–4 g/kg of TA improved the T-SOD, CAT, and GSH-Px activities during infection, while 2 g/kg of dietary TA enhanced the richness and diversity of the microbiota, for example, by increasing Actinobacteria but inhibiting Firmicutes. The transcriptome demonstrated that the predominant differentially expressed genes (DEGs) in TA2 were mainly enriched in the PPAR signaling pathway (Acsl5, Apoa2, Apoa5, Fabp1, Fabp2, and Fabp6); in glycine, serine, and threonine metabolism (Chdh, Gatm, and Shmt1); and in steroid biosynthesis (Cel, Hsd17b7, Soat2, and Sqle). The main differentially expressed metabolites (DEMs) that were discovered by means of metabolome analysis included cholylhistidine, calcipotriol, 13-O-tetradecanoylphorbol 12-acetate, and hexahomomethionine in CG vs. TA2. Integrative analyses of two omics revealed that 2 g/kg of TA mitigated inflammation by activating the PPAR signaling pathway and regulating the lipid metabolism via multiple pathways, such as steroid biosynthesis and α-linolenic acid metabolism. In general, the inclusion of 2 g/kg of TA in turtle diets can optimally promote growth and bacterial resistance by maintaining intestinal health and improving antioxidant capacity.